2015
DOI: 10.1056/nejmoa1509225
|View full text |Cite
|
Sign up to set email alerts
|

Lixisenatide in Patients with Type 2 Diabetes and Acute Coronary Syndrome

Abstract: BACKGROUND: Cardiovascular morbidity and mortality are higher among patients with type 2 diabetes, particularly those with concomitant cardiovascular diseases, than in most other populations. We assessed the effects of lixisenatide, a glucagon-like peptide 1-receptor agonist, on cardiovascular outcomes in patients with type 2 diabetes who had had a recent acute coronary event. METHODS: We randomly assigned patients with type 2 diabetes who had had a myocardial infarction or who had been hospitalized for unstab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
1,395
2
86

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,992 publications
(1,503 citation statements)
references
References 35 publications
20
1,395
2
86
Order By: Relevance
“…10 Recent trials using newer therapies like dipeptidyl peptidase-4 demonstrated non inferiority (safety) in cardiovascular outcomes among patients with T2DM and existing CVD or at higher risk of events. [11][12][13][14] Recently, for example, the use of sitagliptin in more than 7.000 patients -in the TECOS trial -was not associated with an increased risk of heart failure or related adverse outcomes after Sitagliptin therapy.11 There was, however, an increase in the rate of hospitalization for HF with the use of saxagliptin (SAVOR-TIMI 53) trial. 14 The glucagon-like peptide 1 analogue is another type of antidiabetic drugs that had controversial results in outcomes among diabetic patients in recent trials.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recent trials using newer therapies like dipeptidyl peptidase-4 demonstrated non inferiority (safety) in cardiovascular outcomes among patients with T2DM and existing CVD or at higher risk of events. [11][12][13][14] Recently, for example, the use of sitagliptin in more than 7.000 patients -in the TECOS trial -was not associated with an increased risk of heart failure or related adverse outcomes after Sitagliptin therapy.11 There was, however, an increase in the rate of hospitalization for HF with the use of saxagliptin (SAVOR-TIMI 53) trial. 14 The glucagon-like peptide 1 analogue is another type of antidiabetic drugs that had controversial results in outcomes among diabetic patients in recent trials.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the lack of any significant difference in the risk of hospitalizations for HF between those treated with a GLP-1RA or a placebo reported with liraglutide in LEADER [24] was confirmed with lixisenatide in the Evaluation of Lixisenatide in Acute Coronary Syndrome (ELIXA) trial [47] and with semaglutide in the Trial to Evaluate Cardiovascular and Other Long-term Outcomes with Semaglutide in Subjects with Type 2 Diabetes (SUSTAIN-6; Table 4) [48]. Unfortunately, no measurements of pro-BNP levels were available in the LEADER trial [24], and this key information was also missing in the ELIXA [47] and SUSTAIN-6 [48].…”
Section: Lessons From Leadermentioning
confidence: 95%
“…Unfortunately, no measurements of pro-BNP levels were available in the LEADER trial [24], and this key information was also missing in the ELIXA [47] and SUSTAIN-6 [48]. However, such measurements were included in two trials of DPP-4 inhibitors: the EXAMINE with alogliptin [49]; and SAVOR -TIMI 53 with saxagliptin [50].…”
Section: Lessons From Leadermentioning
confidence: 99%
“…In 2015, a third trial testing a DPP-4 inhibitor, the trial Evaluating Cardiovascular Outcomes with Sitagliptin (TECOS) [9], found that the addition of sitagliptin to usual care among patients with glycemic equipoise does not affect rates of major atherosclerotic cardiovascular events, including changes in rates of hospitalization for heart failure [9]. In 2015, the Evaluation of Lixisenatide in Acute Coronary Syndrome (ELIXA) trial [10] reported that another incretin-based therapy, a GLP-1 receptor analogue, did not significantly affect the rate of major cardiovascular events or other serious adverse events in T2DM with a recent acute coronary syndrome.…”
mentioning
confidence: 99%